Sports drinks consumed during exercise, which affect thermoregulation and/or athletic performance in the heat: A review. - Scrivin, R.; Black, K. (Strength and Conditioning Journal, 2018)
It is generally believed consuming sports drinks containing 6-8% carbohadrate and also containing 10-20 mmol[middle dot]L-1 of sodium during endurance events lasting longer than 60 minutes will benefit performance. During exercise in the heat fluis consumption is also important for thermoregulation. Therefore the aim of this review is to investigate the components of a typical sports drink, and determine whether there is any effect on exercise performance or thermoregulation in the heat. The results suggest that carbohydrate ingestion during continuous exercise over 60 minutes in the heat can improve time trila and time to exhaustion performance